Investigating Research Competence Among EFL Learners: Perceptions and Challenges. The Case of Master Two Linguistic Students at the Department of English at M’sila University. - Ilham BAALI, Selsabil Fatima Ezzahra ALLAL (My University, 2020)
Research is a fundamental step in the students’ higher education. It is the point where the students move to the next level from a state of being dependent learners to a more independent state. Nonetheless, many students face several difficulties throughout the research process. Therefore, the current meta-research study attempts prominently to explore the levels of research competence among master one students and to investigate the challenges facing them when developing it. This research adopts a mixed research approach using both a quantitative and a qualitative method following the explanatory mixed method design. To put this methodology into practice, the researchers used the Research Competence Test (RCT) and the students’ questionnaires as instruments to attain the goals of the investigation. In this investigation, thirty (30) master two students at the Department of Letters and English Language at M’sila University are purposely selected as a sample which fits this research scope since they are required to undertake a research projects at the end of the academic year. The results obtained clearly demonstrate the difficulties encountered by the students during their research work. These challenges included inadequate research-related skills, lack of accessible resources, supervisory practices and working in pairs. Henceforth, adequate support and facilitations should be provided by both supervisors and administration to those students undertaking research
Keywords: Key words: Research, Meta-research, Research Competence, Research skills.